Teaching cultural awareness in academic writing skills in EFL classes: Soran and Salahaddin universities as a case study - Mokhles Saleh Ibrahim; Zana Mahmood Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This paper aimed to highlight the impact of teaching cultural awareness in academic writing skills in EFL classes. Also, it tended to answer these research questions: 1- To what extent do Kurdish EFL learners pay attention to cultural aspects of English Academic writing? 2-Would students, who receive teaching English cultural aspects of writing, have better writing productions in terms of including cultural elements of EAW? The quasi-experimental method has been used. Thus, 28 and 27 EFL students were selected for both the experimental and control group from Soran and Salahaddin Universities in Kurdistan Region- Iraq. Essay writing was employed as the data collection instrument for the pre-test and post-test. The results revealed that the participants’ essay writing and academic writing skills in both groups improved. Still, the essay scores of experimental group participants were higher than control group students and significantly enhanced.